The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2109/jcersj2.15319
|View full text |Cite
|
Sign up to set email alerts
|

Gas sensing properties of <i>c</i>-axis-oriented Al-incorporated ZnO films epitaxially grown on (11-20) sapphire substrates using pulsed laser deposition

Abstract: Al-incorporated ZnO films with various Al concentrations were prepared using pulsed laser deposition on the (11 20) face of sapphire substrates, and their gas sensing properties were evaluated. The use of c-axis-oriented epitaxial films with the same thickness suppressed the influence of the surface-to-volume ratio and surface atomic arrangements on the sensing properties, clarifying the role of Al doping in the improvement of ZnO gas sensors. The results of ethanol gas sensing measurements indicated that Al d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…A high sensing response was obtained at 310–350 °C. This agrees with the suitable operating temperature range of 250–400 °C for ethanol sensors using ZnO. As shown in Figure , more time was needed to maintain a constant resistance in ethanol gas at lower temperatures, where the oxidation reaction of ethanol molecules on the ZnO surface is slower compared to that at higher temperatures. At higher temperatures, the sensor response value decreased due to desorption of ethanol.…”
Section: Results and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A high sensing response was obtained at 310–350 °C. This agrees with the suitable operating temperature range of 250–400 °C for ethanol sensors using ZnO. As shown in Figure , more time was needed to maintain a constant resistance in ethanol gas at lower temperatures, where the oxidation reaction of ethanol molecules on the ZnO surface is slower compared to that at higher temperatures. At higher temperatures, the sensor response value decreased due to desorption of ethanol.…”
Section: Results and Discussionsupporting
confidence: 78%
“…It is also widely used in electronic applications, such as varistors, surface acoustic wave filters, transparent electrodes, and phosphors . Control of the morphology of ZnO nanostructures has been intensively investigated, and a wide variety of morphologies (e.g., nanowires, rods, plates, flowers, rings, and spheres) have been observed for particles and thin films. , Various ZnO nanostructures have been studied for gas sensor applications. In our research, we found that the best result for ZnO ethanol sensors was brought by nanoparticles of about 15 nm synthesized via a vapor phase method . The sensor response (ratio of electrical resistance in air to that in ethanol gas) to 50 ppm ethanol gas in air was about 500 at 400 °C.…”
Section: Introductionmentioning
confidence: 80%
“…It is worthwhile to note that the ZnO sample exhibits a large S of 21 with an R air saturate of about 6 GΩ. It is a surprisingly large sensitivity by considering that the ZnO single-crystalline thin film with a thickness of several tens of nanometers has an S of 10–20 ( Figure S1 and refs ( 22 ) and ( 37 )). The relationship between S and R air saturate in Figure 2 c indicates that S may further increase with the increase of R air saturate .…”
Section: Resultsmentioning
confidence: 99%
“…The details of the apparatus have been described elsewhere. 37 Briefly, the apparatus has essentially the same design as that for evaluating gas sensing properties by the conventional two-terminal method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation